2016
DOI: 10.1590/s0102-865020160110000010
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis model induced by intra-articular monosodium iodoacetate in rats knee

Abstract: PURPOSE:To evaluate the usefulness of a knee osteoarthritis model through functional, radiological and microscopic changes of the synovial membrane. METHODS:Forty eight rats were divided randomly into two groups. The first received 0.9% saline in the joint and corresponded to the control group. The second was submitted to experimental osteoarthritis of the right knee induced by monosodium iodoacetate and corresponded to the osteoarthritis group. All animals were subjected to comparative tests of forced ambulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
(29 reference statements)
3
11
0
1
Order By: Relevance
“…Animal experiments were carried out according to the protocols approved by Chongqing University Animal Care and Use Committee. According to the references 19, 20, OA was induced by a single intra-articular knee injection of monosodium iodoacetate (MIA) (Sigma) (6 mg/kg body weight, 50 μL) into the bilateral knee-joints of the Sprague-Dawley (SD) rats (200-250g). Two weeks followed by MIA injection, the rats had their knee-joints treated with 1 mg/kg (body weight) of PSO (MIA+PSO group) and sterile saline solution (MIA group) via intra-articular knee injection daily for 1 week, and once every three days for another 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments were carried out according to the protocols approved by Chongqing University Animal Care and Use Committee. According to the references 19, 20, OA was induced by a single intra-articular knee injection of monosodium iodoacetate (MIA) (Sigma) (6 mg/kg body weight, 50 μL) into the bilateral knee-joints of the Sprague-Dawley (SD) rats (200-250g). Two weeks followed by MIA injection, the rats had their knee-joints treated with 1 mg/kg (body weight) of PSO (MIA+PSO group) and sterile saline solution (MIA group) via intra-articular knee injection daily for 1 week, and once every three days for another 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…A doença articular degenerativa é denominada de osteoartrose, osteoartrite ou artrite degenerativa, é definida pelo Colégio Americano de Reumatologia como um conjunto de alterações que induzem sintomas e sinais dolorosos articulares associados a defeitos na integridade da cartilagem articular e da membrana sinovial, levando a alterações na margem óssea articular. (MORAIS et al, 2016). É um grupo de doenças e alterações mecânicas que interferem na degradação da cartilagem articular e do osso subcondral, ocasionando diminuição da amplitude dos movimentos.…”
Section: Introductionunclassified
“…The MIA model is commonly used as an arthritis model mimicking human OA for pain assessment, owing to the consistent pain-like responses throughout the modeling period [23]. It provides measurable changes on joint movements, tactile allodynia, inflammation, and progressive cartilage degeneration that represent markers for OA evaluation [24]. Previous studies reported that the MIA model is useful for evaluating the pathology of non-traumatic OA, pain mechanisms, and therapeutic effects on cartilage [25, 26].…”
Section: Introductionmentioning
confidence: 99%